IABSE Symposium, Venice 2010: Large Structures and Infrastructures for Environmentally Constrained and Urbanised Areas 2010
DOI: 10.2749/222137810796025609
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Highway Vehicle Load in China Based on WIM Data

Abstract: <p>The current general design code for highway bridge in China is the<i>General Code for Design of Highway Bridges and Culverts (JTG D60-2004)</i>, in which clauses on vehicle live load is generalized from statistics of vehicles on four national highways during the 90s, including National Highway No. 207 and No. 328. Recently, vehicle load on bridges has significantly changed due to the construction and operation of a large number of highways with distinctive vehicle types, speed, weight, etc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Total numbers and percentages of every vehicle type were obtained for each province according to vehicle classification given in the previous section, as shown in Table 3. In previous studies on vehicle load data, it is indicated that small passenger cars, large and medium-sized passenger cars, and 2-axle goods vehicles are the most frequent vehicle types encountered on motorways [33,34]. In this paper, the data of vehicles weighing less than 30 kN were excluded from data processing, where the number of the small passenger car is the largest.…”
Section: Vehicle Load Analysismentioning
confidence: 99%
“…Total numbers and percentages of every vehicle type were obtained for each province according to vehicle classification given in the previous section, as shown in Table 3. In previous studies on vehicle load data, it is indicated that small passenger cars, large and medium-sized passenger cars, and 2-axle goods vehicles are the most frequent vehicle types encountered on motorways [33,34]. In this paper, the data of vehicles weighing less than 30 kN were excluded from data processing, where the number of the small passenger car is the largest.…”
Section: Vehicle Load Analysismentioning
confidence: 99%